Magnetic resonance features of sinonasal melanotic mucosal melanoma. Issue 7 (22nd July 2019) - Nardi, Cosimo; Vignoli, Chiara; Vannucchi, Margherita; Pietragalla, Michele
Abstract : A 67-year-old man presented to ear, nose and throat department complaining of nasal congestion and recurrent epistaxis for 5 months. Nasal endoscopy revealed a pigmented polyp obstructing the right nasal cavity. MRI with contrast agent showed a right nasal cavity polypoid mass with hyper signal intensity (SI) both in non-enhanced T1-w and diffusion imaging, marked hypo SI in T2-w sequences and avidly contrast enhancement characterised by rapid wash-in without significant wash-out on dynamic perfusion imaging. Histological specimen showed epithelioid and spindle cells with focal intense pigmentations and immunohistochemical features compatible with primary melanotic sinonasal mucosal melanoma (SNM). As melanotic SNM shows MRI pathognomonic high non-enhanced T1-w SI, this case underlines the crucial role of MRI not only in assessing the local tumour extension/recurrence but also in increasing the diagnostic confidence of detecting melanotic SNM. Thus, MRI should be always performed in case of clinical–endoscopic suspicion of SNM.